Carrying eggs in a semi-terrestrial environment: Physiological responses to water deprivation of mothers and embryos of the tree-climbing crab Aratus pisonii - Marochi, Murilo Zanetti [UNESP]; Castellano, Giovanna Carstens; Freire, Carolina Arruda; Masunari, Setuko (Elsevier, 2021)
In semi-terrestrial crustaceans, mothers and the carried embryos form a unit. The ideal conditions for embryonic development place a sustained demand on the mothers' energy budget. A particular challenge for this unit is the transition between terrestrial and aquatic environments. Ecophysiological information on mothers and embryos contributes to the understanding of evolutionary pathways and constraints of terrestrialization in crabs. We evaluated the effects of 6, 12, and 18 h of water deprivation on embryonic development and maternal physiology of the tree-climbing crab Aratus pisonii (H. Milne Edwards, 1837). Specifically, we determined the effect of water deprivation on egg volume, osmolality, and larval survival, as well as on maternal body mass, hemolymph osmolality, and branchial carbonic anhydrase activity (CAA). We hypothesized that longer periods of water deprivation would negatively affect larvae viability, as well as disrupt the physiology of brooding females. Embryonic development, larval survival, and the mother's physiology were only altered after 18 h of water deprivation, possibly due to dehydration and/or the accumulation of metabolic wastes that could not be excreted in the absence of water. Osmolality was higher in females than in their eggs. CAA of the anterior gills was higher in ovigerous than in non-ovigerous females, possibly due to the increase in respiratory demands caused by carrying eggs. Our results confirmed that the gestation period represents a metabolically expensive period for mother crabs and that water deprivation of 18 h was critical for the embryos' survival.
Keywords: Carbonic anhydrase; Dehydration; Larval survival; Osmolality; Osmotic stress; Terrestrialization